Ocorrência de ácaros e alérgenos em veículos de transporte público - Pereira, Fernando Lourenco (2004)
Mites and pets are important sources of indoor allergens in public transport vehicles that couid represent a serious problem in sensitized subjects. The aim of this study was to determine Der p 1, Der f 1 and Fel d 1 allergen leveis in buses and taxis, and to evaluate the predominant allergen in each public transport vehicle. Mite and cat allergens were measured by a sandwich ELISA in dust samples coilected from upholstered seats of 60 natural ventilation buses (NVB), 60 artificial ventilation buses (AVB) and 60 taxis. Thirty dust samples from air-conditioning filters of AVB were also included. Der p 1 and Der f 1 leveis were significantly higher in AVB than NVB, while Fel 1 leveis were not significantly different between the types of buses. No significant differences were found for mite allergen leveis in various sites of both types of buses, whereas Fel d 1 leveis were significantly higher in rear and middle than front seats in NVB. Mite and cat allergen leveis in taxis were significantly higher in passengeris rear than driveris seats. A high proportion of dust samples of vehicles, especially AVB (82% for Der p 1 and 58% for Der f 1) had sensiíizing leveis for mite allergens, while > 60% of samples from all vehicles had sensitizing leveis for Fel d 1 allergen. Samples from seats showed significantly higher leveis of mite and cat allergens than air-conditioning filter of AVB. It can be concluded that public transport vehicles constitute an important allergen reservoir for continuous contamination of the indoor environment. Health professionals should be aware of this additional possibility of allergen exposure on medicai management of their mite and cat sensitized patients.